2022
DOI: 10.3390/life12020243
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light-Induced Retinal Neuronal Injury and Amelioration by Commercially Available Blue Light-Blocking Lenses

Abstract: Blue light exposure-induced retinal damage has been extensively studied. Although many in vitro studies have shown the benefits of blue light-blocking lenses (BBL) there have been few comprehensive in vivo studies to assess the effects of BBL. We investigated the influence of blue light exposure using light-emitting diodes on retinal histology and visual cortex neurons in rodents. We also considered whether retinal and cortical changes induced by blue light could be ameliorated with blue light-blocking lenses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
5
0
1
Order By: Relevance
“…In a previous study employing the same light exposure protocol, the retina was thinned and neurons in layer 5 of the visual cortex were negatively impacted, particularly with reductions in basal dendrites [31,45]. The current data show that similar changes were also present in the hippocampus.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In a previous study employing the same light exposure protocol, the retina was thinned and neurons in layer 5 of the visual cortex were negatively impacted, particularly with reductions in basal dendrites [31,45]. The current data show that similar changes were also present in the hippocampus.…”
Section: Discussionsupporting
confidence: 71%
“…Ours and other studies have shown that the retina is severely damaged by prolonged exposure to short-wavelength light [14,31,50]. Even after the degeneration of photoreceptors, there was evidence of ongoing apoptotic activity, as indicated by caspase 3 staining of the inner retinal and retinal ganglion cells [31]. It is likely that such injury would result in altered input into the hippocampus from ipRGCs.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the interim, it is crucial to minimize excessive light exposure. Several measures have been proposed to achieve this [ 13 , 168 , 169 , 170 ]. Exposure to morning sunlight is recommended to help maintain synchronized rhythms, along with the use of blue light cutting glasses and blue light cutting base makeup.…”
Section: Discussionmentioning
confidence: 99%
“…The white and blue LEDs have high energetic characteristics compared with other traditional light sources, so the potential ocular and general risks of these LEDs are widely explored [ 4 , 19 , 21 , 22 , 23 , 24 , 25 ]. The short-term (28 days) exposure to moderate blue light causes nebulous metabolites in the vitreous [ 26 ] and changes in retinal tissues and cortical neurons [ 27 , 28 ]. Inference from these studies cannot be generalized because few studies have suggested that low levels of blue light for a longer duration (a few months to years) are needed to determine the effects of blue light on the visual system [ 29 ].…”
Section: Introductionmentioning
confidence: 99%